2008
DOI: 10.1364/ao.47.005750
|View full text |Cite
|
Sign up to set email alerts
|

Planar waveguide obtained by burying a Ge_22As_20Se_58 fiber in As_2S_3 glass

Abstract: We demonstrate the possibility of fabricating an infrared transmitting waveguide by burying fiber in chalcogenide glasses. Two highly mature chalcogenide glasses are used for these experiments. GASIR glass from Umicore IR Glass, Olen, Belgium, with the composition of Ge 22 As 20 Se 58 is used to draw fibers that are then buried in an As 2 S 3 glass substrate. The glasses we used are compatible, and we obtained a high quality interface. We performed a transmission test with a CO 2 laser at 9:3 μm. The potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…There has been some progress toward volumetric photonic integration, i.e., beyond two-dimensional planar waveguides and toward making three-dimensional (3-D) waveguides. Thus, Coulombier et al 17 have demonstrated burying a fiber in bulk glass. Also, high intensity fs laser *Address all correspondence to: Angela B. Seddon, E-mail: angela.seddon@ nottingham.ac.uk 3-D writing at 1.55-μm wavelength has been used to make waveguides by means of effecting photorefraction in the volume of a bulk glass; the photorefraction relies on the innately very high optical nonlinearities of chalcogenide glasses.…”
Section: Introductionmentioning
confidence: 99%
“…There has been some progress toward volumetric photonic integration, i.e., beyond two-dimensional planar waveguides and toward making three-dimensional (3-D) waveguides. Thus, Coulombier et al 17 have demonstrated burying a fiber in bulk glass. Also, high intensity fs laser *Address all correspondence to: Angela B. Seddon, E-mail: angela.seddon@ nottingham.ac.uk 3-D writing at 1.55-μm wavelength has been used to make waveguides by means of effecting photorefraction in the volume of a bulk glass; the photorefraction relies on the innately very high optical nonlinearities of chalcogenide glasses.…”
Section: Introductionmentioning
confidence: 99%